Investigating The Sustainable Development of Tabriz University Based on Green Management Parameters and Preferences of University Managers - Bolouri, Farhad; Zarghami, Mahdi (Universitas Diponegoro, 2021)
In recent years, the destruction of the environment on the one hand and the increase in awareness of the consequences of this great danger on the other hand, has led to global actions and consequently, local actions to protect the environment and sustainable development. One of these actions is the sustainable development of universities. The reason for the importance of this case is, firstly, the goal of the universities themselves, which as the center of knowledge and training of the country's elites, is also at the top of environmental affairs, and secondly, as a center with a large number of students and staff which can have a great impact with action for environment. In this research, by using library studies, field observations and interviews, we try to identify sustainability measures of Iranian universities in order to achieve sustainable development and finally present the results of these measures to improve the methods of establishing sustainable development in universities and provide a comprehensive and complete model taking into account all aspects of sustainable development in universities with special emphasis on the campus and its green management. A questionnaire-based on international and domestic standards on the effectiveness of green management parameters in the sustainable development of Tabriz University was prepared and sent to university administrators and faculty members, and then the top ten rankings of this questionnaire were used using interviews with Tabriz university administrators to be determined their preferences in this regard.